2002
DOI: 10.1071/ar01100
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional strategies for the prevention of hypocalcaemia at calving for dairy cows in pasture-based systems

Abstract: This review considers the current literature on the macro-mineral nutrition of the soon-to-calve, or transition, dairy cow. Calcium is the main focus, since milk fever (clinical hypocalcaemia) appears to be the most common mineral-related problem faced by the transition cow Australia-wide. The importance of minimising calcium intake and optimising the balance of the key dietary electrolytes, sodium, potassium, sulfate, and chloride, in the weeks before calving is highlighted. Excess dietary potassium can, in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Strategies to prevent milk fever now focus on the use of forages with moderate to low levels of Ca, K and Na, such as maize silage or silage from other cereals (Taube et al. , 1995; McNeill et al. , 2002).…”
Section: Implications Of Potassium For Animal Health and Nutritionmentioning
confidence: 99%
“…Strategies to prevent milk fever now focus on the use of forages with moderate to low levels of Ca, K and Na, such as maize silage or silage from other cereals (Taube et al. , 1995; McNeill et al. , 2002).…”
Section: Implications Of Potassium For Animal Health and Nutritionmentioning
confidence: 99%
“…In situations of high‐positive DCAD and alkaline urine, changes in urine pH are small when DCAD decreases (Roche et al., 2003). In fact, McNeill et al. (2002) observed that urine pH is unlikely to respond before DCAD is reduced below 200 meq/kg DM.…”
Section: Discussionmentioning
confidence: 99%
“…grains, hay and silage). 9 An incidence of subclinical hypocalcaemia of approximately 67% and 80% has been reported for dairy farms in the subtropics 10 and southern districts (Victoria) of Australia, 11 respectively. 2 Although the average herd size has increased from 85 to 220 cows, the yield per cow has also increased from 2850 to 5500 L/cow per lactation, which is a result of improved intensive genetic selection as well as improved nutritional and farm management practices.…”
mentioning
confidence: 99%